2013
DOI: 10.1107/s0909049513021572
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of haemoglobin from pisces species shortfin mako shark (Isurus oxyrinchus)at 1.9 Å resolution

Abstract: Haemoglobin (Hb) is a tetrameric iron-containing protein that carries oxygen from the lungs to tissues and carbon dioxide from tissues back to the lungs. Pisces are the advanced aquatic vertebrates capable of surviving at wide depth ranges. The shortfin mako shark (SMS) is the pelagic, largest, fastest and most sophisticated species of the shark kingdom with well developed eyes. Mostly the pisces species are cold blooded in nature. Distinctly, the SMSs are warmblooded animals with an advanced circulatory syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Mouse Hb was purified using previously reported procedures (Sundaresan et al, 2009;Ramesh et al, 2013). In brief, fresh blood collected from mice was mixed with 10%(w/v) ethylenediaminetetraacetic acid (EDTA) to avoid clotting.…”
Section: Purification and Crystallizationmentioning
confidence: 99%
“…Mouse Hb was purified using previously reported procedures (Sundaresan et al, 2009;Ramesh et al, 2013). In brief, fresh blood collected from mice was mixed with 10%(w/v) ethylenediaminetetraacetic acid (EDTA) to avoid clotting.…”
Section: Purification and Crystallizationmentioning
confidence: 99%
“…The following is a response to the points raised in the comment by Merlino et al on our recent paper on haemoglobin (Hb) from the shortfin mako shark (SMS) (Ramesh et al, 2013).…”
mentioning
confidence: 98%
“…With regard to those two states, our SMS Hb belongs to the deoxy T state conformation, and we confirmed that there is no ligand in the heme binding pocket, such as CO and O 2 , in SMS Hb. We therefore concluded that SMS Hb belongs to the deoxy unliganded T state conformation (Ramesh et al, 2013). We first purified native protein from shark blood and then performed the crystallization directly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent paper by Ramesh et al (2013) reports a crystallographic study on the tetrameric haemoglobin (Hb) isolated from the shortfin mako shark (Isurus oxyrinchus) (SMS). From the analysis of the overall and local features of the model the authors conclude that the structure corresponds to an unliganded deoxy T state conformation.…”
mentioning
confidence: 99%